HAOGUMI LEXICON: LOCAL WISDOM OF THE COMMUNITY OF GALOGALO VILLAGE, MOROTAI ISLAND REGENCY, NORTH MALUKU A ETHNOLINGUISTICS STUDIES (LEKSIKON HAOGUMI: KEARIFAN LOKAL MASYARAKAT DESA GALOGALO, KABUPATEN PULAU MOROTAI, MALUKU UTARA SEBUAH KAJIAN ETNOLINGUISTIK) - Mujahid Taha; Fida Febriningsih (Jurnal Gramatika, 2022)
The Galela ethnicity who live in Galogalo Village, South Morotai District, Morotai Island Regency, North Maluku Province until now still maintain and believe in the tradition of local wisdom of their ancestors, namely haogumi (knowledge and belief in catching fish). Haogumi is a traditional fishing technique that involves the community as the owner of the local wisdom tradition. Maintaining and preserving haogumi amidst the onslaught of modernization is a strategic step in protecting local wisdom in a society increasingly eroded by the times. One of the functions of haogumi is to maintain the natural environment and the behaviour of the people around it. This research aims to describe the haogumi local wisdom tradition contained in the community as knowledge and belief in catching fish. This article uses ethnolinguistic research through qualitative descriptive methods. The research results show that the Galela ethnic who lived in Galogalo Village once had a tradition of local wisdom in the form of haogumi. The traditional lexicon of local wisdom forms is: 1. haogumi; 2. ok higaro ma; 3. kugi; 4. kota; and 5. bori.